Peripheral Blood Inflammatory-Immune Cells as a Predictor of Infertility in Women with Polycystic Ovary Syndrome - He S (Dove Medical Press, 2020)
ShuQiong He,1,* XiaoDan Mao,2,3,* HuiFang Lei,2,3 BinHua Dong,2,3 DanHua Guo,1 BeiHong Zheng,4 PengMing Sun2,3 1Department of Prenatal Diagnosis, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, 350001, People’s Republic of China; 2Laboratory of Gynecologic Oncology, Department of Gynecology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, 350001, People’s Republic of China; 3Fujian Key Laboratory of Women and Children’s Critical Diseases Research, Fujian Maternity and Child Health Hospital, Fuzhou, 350001, People’s Republic of China; 4Department of Reproduction, Fujian, Affiliated Hospital of Fujian Medical University, Fuzhou, 350001, People’s Republic of China*These authors contributed equally to this workCorrespondence: PengMing SunLaboratory of Gynecologic Oncology, Department of Gynecology, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, No. 18 Daoshan Road, Fuzhou 350001, Fujian, P.R. of ChinaEmail sunfemy@hotmail.comPurpose: This study aimed to investigate the inflammatory-immune cells in the peripheral blood of women with polycystic ovary syndrome (PCOS) and assessed the potential correlation between inflammatory-immune cells and infertility in PCOS women.Materials and Methods: In this case–control study, the profiles of lymphocyte subsets were analyzed by flow cytometry. White blood cells (WBC), neutrophils (Neu), lymphocytes, Ferriman–Gallwey (F–G) score, testosterone, prolactin, follicle-stimulating hormone, luteinizing hormone, fasting blood glucose, and fasting plasma insulin were measured, together with body mass index. Association between inflammatory-immune cells and PCOS was evaluated. Moreover, inflammatory-immune cells of the PCOS women with infertility were evaluated, and the relative operating characteristic (ROC) curve and cutoff values were calculated.Results: The number of WBC, Neu, and lymphocytes was higher in PCOS women than controls (P< 0.05). The percentages of total T lymphocytes, CD4+T, and NK were significantly increased in the PCOS group (P< 0.001). The CD4/CD8 ratio was obviously elevated for increasing CD4+T (P< 0.05). Consequently, T%, CD4+T%, and NK% were found to be the independent risk factors of PCOS by ROC curve and multivariate logistic regression analysis. Furthermore, only NK% was significantly higher in PCOS women with infertility than those who had PCOS without infertility (P< 0.001). To diagnose infertility in PCOS, the cutoff value of NK% was calculated as 16.43%.Conclusion: These findings suggest that the pathogenesis of PCOS is related to immune cells including T, CD4+T, and NK cells. NK cells are likely to be a potential predictive factor for PCOS women with infertility.Keywords: lymphocyte subsets, inflammatory cells, natural killer cells, immunocompetent cells, pathogenesis